2016
DOI: 10.1159/000443432
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Opossum Kidney Cells to Luminal Phosphate: Effects of Phosphonoformic Acid and Kinase Inhibitors

Abstract: Background/Aims: Renal reabsorption of inorganic phosphate (Pi) is mediated by SLC34 and SLC20 Na+/Pi-cotransporters the abundance of which is under hormonal control. Extracellular Pi itself also regulates the expression of cotransporters and the concentration of Pi-regulating hormones, though the signaling pathways are largely unknown. Here, we explored the mechanisms that allow renal proximal cells to adapt to changes in the concentration of Pi. Methods: opossum kidney (OK) cells, a model of proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Our data in Npt2a-I-treated OK cells demonstrate, compared with vehicle, a significantly higher K m with no significant change in the apparent V max , consistent with a competitive pattern of inhibition. OK cells respond to increasing concentrations of P i in the media with inverse changes on Na ϩ -dependent P i uptake and Npt2a expression (47,58). Regarding the former, our data confirm these findings.…”
Section: F548supporting
confidence: 85%
See 1 more Smart Citation
“…Our data in Npt2a-I-treated OK cells demonstrate, compared with vehicle, a significantly higher K m with no significant change in the apparent V max , consistent with a competitive pattern of inhibition. OK cells respond to increasing concentrations of P i in the media with inverse changes on Na ϩ -dependent P i uptake and Npt2a expression (47,58). Regarding the former, our data confirm these findings.…”
Section: F548supporting
confidence: 85%
“…The medium was changed every 3 days, and cells were split 1:3 once per week by trypsinization. Low-Pi (0.1 mmol/L) or high-Pi (2 mmol/L) medium was made using Pi-free medium (GIBCO) (47,58) supplemented with the desired Pi concentrations (Na2HPO4/NaH2PO4, pH 7.4) along with penicillin-streptomycin (50 IU/mL) and HEPES (20 mmol/L, GIBCO). Experiments were done between passages 45 and 60.…”
Section: Methodsmentioning
confidence: 99%
“…4C and 4D). Previous reports revealed that extracellular or intracellular ATP levels regulate Na + -dependent Pi transport activities in the proximal tubular cells [34,46]. To determine the reason for the reduced Npt2b protein expression, we hypothesized that ATP, which is a substrate of Akp3, is involved in regulating Npt2b expression.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to NaPiIIa (e.g. Markovich et al., ; Pfister et al., ; Thomas, Wagner, Biber, & Hernando, ; Villa‐Bellosta & Sorribas, ), adaptation to a low P i concentration in a culture medium also affects NaPiIIc RNA in OK cells (Figure ). In the case of NaPiIIa (Markovich et al., ) and most probably regarding NaPiIIc, the increase in mRNA seems to be attributable to an increased stability of RNA rather than increased transcription.…”
Section: Discussionmentioning
confidence: 99%